AVALIAÇÃO DE CARACTERÍSTICAS BIOLÓGICAS DE TRICHOGRAMMA PRETIOSUM RILEY (HYMENOPTERA: TRICHOGRAMMATIDAE) CRIADO EM TRÊS HOSPEDEIROS - Volpe, H.x.l. [UNESP] (2022)
Trichogramma genus are very important on biological control, since that its potential was discovered, its very useful worldwide as a option for pest control in different agroecosystems, making indispensable the knowledge of different hosts for these parasitoids. The aim of this work was to evaluate T. pretiosum specificity in relation to three host species. The research was conducted at Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal (FCAV-UNESP), in the Laboratório de Biologia e Criação de Insetos. It was realized test of choice (no choice) in relation to Anagasta kuehniella, Spodoptera frugiperda and Plutella xylostella eggs handled under laboratory conditions. By the tests it was possible to verify differences for the number of parasitized eggs, being A. kuehniella preferred in the first and second generation, but no differences were founded for adults emergence. In the second generation, the higher number of parasitized eggs was observed for Anagasta kuehniella and Spodoptera frugiperda, differing of Plutella xylostella. By the results its possible to conclude that T. pretiosum Tp – 8 strain had better adaptation to the host A. kuehniella and the strain of Trichogramma pretiosum was viable to be used in Biological Control programs, to control Spodoptera frugiperda and Plutella xylostella.